Putusan Hakim Terhadap Tindak Pidana Pencurian 2 (dua) Lembar Besi Plat Warna Hijau (Studi Kasus Putusan Nomor 1357/Pid.B/2023/PN Mdn) - Nurul Azmy Pratiwi; Ibda Maghni Tarigan; Sadnes Sinaga; Parlaungan Gabriel Siahaan; Dewi Pika Lbn Batu (Jurnal Multidisiplin Dehasen (MUDE), 2024)
The research is entitled "Judge's Decision Regarding the Crime of Theft of 2 (two) Green Metal Plates (Case Study Decision Number 1357/Pid.B/2023/PN Mdn)". The crime of theft is increasing and developing rapidly, causing the security of a country to be disrupted. This is a negative impact of the progress that has been achieved by a country. The crime of theft committed by many people is caused by economic factors which are getting worse due to low income and also The high unemployment rate is because it is difficult to find work. Other factors that support someone committing the crime of theft include environmental influences, the opportunity to commit theft, lack of awareness of the law by the perpetrator and can be caused by other social factors. This research is descriptive analytical in nature with the aim of describing a research object or data as thoroughly as possible which contains explanations about humans, conditions or various kinds of symptoms to emphasize several types of hypotheses to make it easier to strengthen theories with the ultimate aim of making a comprehensive conclusion. the results of the research are that the defendant Wawan M. Nur has been legally and convincingly proven guilty of committing the crime of "theft under aggravating circumstances"; as in the public prosecutor's single indictment; namely the Defendant together with Mr. SUKMA (DPO) in taking 2 (two) pieces of green iron plate 5 (five) millimeters thick with a size of 150cm x 40cm without the knowledge and/or permission of Witness ROBERT H as Tembekang Belawan Pusbekangad TNI AD's attorney as the owner, which caused the TNI AD Tembekang Belawan Pusbekangad suffered a loss of approximately Rp. 5,000,000 (five million rupiah). The judge's decision is a decision that has been reviewed as carefully as possible and thoroughly, therefore a prison sentence of 3 (three) years and 6 (six) months for the defendant is a fair decision for the defendant and also the victim. Thus, it is hoped that from this case no one else will commit acts of theft which could be detrimental to the perpetrator and victim if discovered, and from this case it can also have a deterrent effect on the defendant so that they do not commit other criminal acts and from this case it can give fear to the accused. readers not to commit acts that can be punished.